Economics and Constraints Analysis of Cotton in Nalgonda District of Telangana - Haripriya, Siripuram; Bandumula, Nirmala; Suhasini , K.; Savitha, B.; Rathod, Santosha (International Journal of Economic Plants, 2025)
The study was conducted from December to March, 2024–25 in the Nalgonda district. Telangana, India, to assess the economics of cotton cultivation in the district. Cotton is one of the most important commercial crops and plays a pivotal role in the income of rural households in the district. A sample of 60 farmers was selected using a simple random sampling technique without replacement, and data were collected through a personal interview method during 2024–25. The results revealed that the total cost of cotton cultivation was Rs. 84693 ha-1, comprising Rs. 64586 ha-1 (76.26%) as operational cost and Rs. 20107 ha-1 (23.74%) as fixed cost. Among the various input costs, human labour was the major cost, Rs. 27021 ha-1, followed by plant protection chemicals and fertilizer costs, Rs. 10082 ha-1 and Rs. 9152 ha-1, respectively. The average yield was 19.74 q ha-1, and gross returns were found to be Rs. 149346 ha-1. The B:C ratio was 1.76, which indicated that the cotton crop is profitable in the study area. The major constraints faced by cotton growers were the high wage rate of labour for cotton picking, infestation of the pink bollworm, and lack of awareness of the scientific method of cotton cultivation. Mechanised cotton picking reduces labour costs and increases net returns, emphasizing the need for state government incentives to support the mechanisation in cotton picking.